Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik di Kelas II SD - Rosmanita, Rosmanita; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research purposed to describe the improvement of integrated thematic learnig process using Scientific Approach Grade II in Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 14 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection .The result of planning observation in cycle I is 81,81% (B) and it increase to be 90,90% (A)  in cycle II. The result of teacher aspect observation in cycle I is 77,5% (C)  and it increase to be 95% (A) in cycle II. The result of student aspect observation in cycle I is 67,5% (C)  and it increase to be 90% (A) in cycle II. The learning outcomes in cycle I is 75(C) and it increase to be 88,21 (A) in cycle II. The research showed the scientific approach can improve the integrated thematic learnig process Grade II at Elementary School.